Tip 1 Diyabetli 6 Yaştan Küçük ve Büyük Çocukların Tanı Anındaki Farklılıkları - Kirkaş, Özlem Gül; Demirel, Fatma; Köse, Gülşen; Esen, İhsan (T.C. Sağlık Bakanlığı Ankara Şehir Hastanesi, 2014)
Amaç: Son zamanlarda özellikle 6 yaş altındaki çocuklarda Tip 1 diabetes mellitus (T1DM) insidansında artış olmuştur. Bu çalışmanın amacı, küçük yaş ve daha büyük yaşlardaki T1DM’lu çocukların tanı anındaki klinik ve laboratuvar farklılıklarını analiz etmektir.Gereç ve Yöntemler: Ankara Çocuk Sağlığı Hastalıkları Hematoloji Onkoloji Hastanesi pediatrik endokrin bölümünde geçen 10 yılda T1DM tanısı alan 99 çocuğun dosyası (49 hasta ?6 yaş, 50 hasta >6 yaş) geriye dönük incelendi. Kliniğe ilk başvuru anındaki klinik ve laboratuvar bulguları değerlendirildi.Bulgular: Yaşça küçük olan grupta, ortalama semptomların ortaya çıkış süresi daha kısa (15.2±1.9 ve 27.7±5.1 gün) ancak insülin infüzyonundan subkutan insülin geçiş süresi daha uzun (17.1±1.3 ve 13.6±1.2 saat)’di. Kilo kaybı semptomu büyük çocuklarda daha sık ve HbA1c düzeyi küçük çocuklarda anlamlı olarak daha düşüktü. Küçük çocuklarda diyabet ilişkili antikorlardan en az birinde pozitiflik anlamlı olarak daha fazlaydı (p<0,05).Sonuç: Bu çalışma, küçük ve daha büyük yaştaki diyabetik çocukların hastaneye ilk başvuru anındaki klinik ve laboratuvar bulgularındaki farklılıkları göstermektedir ve bu farklılıkların ortaya konması, diyabet ekibinin bu hastaların tanı, tedavi ve izleminde yol gösterici olacaktır.

Objective: There has recently been an increase in the incidence of Type 1 diabetes mellitus (T1DM), particularly among younger children. The purpose of the present study was to analyze the differences in the clinical and laboratory fi ndings at presentation between the younger (?6 years of age) and older (>6 years of age) groups of patients with T1DM. Material and Methods: A retrospective scan was performed on the hospital data of 99 children with T1DM registered during the past 10 years at the pediatric endocrinology clinic of Ankara Children’s Haematology Oncology Training Hospital (49 patients were ?6 years old and 50 were >6 years old). The clinical and laboratory fi ndings at the fi rst presentation to the clinic were reviewed.Results: The mean duration of symptoms before presentation was shorter (15.2±1.9 and 27.7±5.1 days respectively) in the younger age group. The transition time from intravenous insulin to subcutaneous treatment was signifi cantly longer than in the older patients (17.1±1.3 and 13.6±1.2 hours respectively). Weight loss was found to be more signifi cant among older children and HbA1c was signifi cantly lower in the younger age group. A signifi cantly higher proportion of patients in the younger group was found to be positive for at least one of the diabetes-associated antibodies (p<0.05).Conclusion: Elucidation of clinical and laboratory differences between younger and older diabetic children at the time of diagnosis would provide guidance for diabetes care teams in the diagnosis, treatment and monitoring of these patients
Differences in Children with Type 1 Diabetes Aged ifferences in Children with Type 1 Diabetes Aged ?6 and >6 Years at the Time of Diagnosis